104k views
4 votes
(-16t - 2)(t - 5) is the same as 10+78t-16t^2 but in factored form. Explain how you know,

basically help me convert the factored form into the standard form

User Bkribbs
by
4.5k points

1 Answer

5 votes

Answer:

10+78t-16t^2

Explanation:

(-16t-2)(t-5)

-16t × t= -16t²

-16t × -5=80t

-2 × t= -2t

-2 × -5=10

-16t²+80t-2t+10= -16t^2+78+10

User Henrik Pingel
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.